Density functional static dipole polarizability and first-hyperpolarizability calculations of Na-n (n=2, 4, 6, 8) clusters using an approximate CPKS method and its comparison with MP2 calculations - Sophy, K. B.; Calaminici, Patrizia; Pal, Sourav (Journal of Chemical Theory and Computation, 2007)
{We report the static dipole polarizability and first-hyperpolarizability of the sodium atom clusters, Na-n